The Family as the Domestic Church: An Empirical Study of Christian Spirituality Formation in Early Childhood Within a Parish Pastoral Framework - Marcelina Intan Trisnawati; Nerita Setiyaningtiyas; Gregorius Daru Wijoyoko; Tomotius Tote Jelahu (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This article investigates how Christian spirituality is cultivated in children aged three to seven years through active parental engagement within the pastoral setting of Santo Isidorus Parish, Sukorejo, Kendal Regency, Central Java. The study departs from an observed tension between the Church's theological vision of the family as a domestic church and the actual minimal faith guidance found in many Catholic households. Three research objectives guide the inquiry: describing the forms of parental faith accompaniment, identifying both enabling and constraining factors, and devising strategies to elevate accompaniment quality. A descriptive qualitative design was adopted, employing semi-structured in-depth interviews with twelve purposively selected informants comprising the parish priest, the coordinator and facilitators of the Children's Faith Formation program, as well as active and less active parents. Data were analysed through Miles and Huberman's interactive model, with credibility secured via source and method triangulation. Findings reveal that parents guide their children through regular communal prayer, consistent Sunday church attendance, age-appropriate biblical narration, embodied Christian witness, and ongoing moral mentorship. The primary enabling conditions are parental theological conviction and supportive parish programming, whereas the chief constraints consist of demanding work schedules, physical exhaustion, excessive screen exposure, and limited practical knowledge of faith accompaniment. Five interconnected strategies emerge from the data: developing family-centred parish initiatives, strengthening relational communication between facilitators and parents, producing accessible devotional resources, fostering collaborative partnership among parish actors, and empowering parents through sustained catechetical formation.